2021
DOI: 10.3171/2021.6.peds21162
|View full text |Cite
|
Sign up to set email alerts
|

Elevated intracranial pressure with craniosynostosis: a multivariate model of age, syndromic status, and number of involved cranial sutures

Abstract: OBJECTIVE Children with multiple prematurely fused cranial sutures and those undergoing surgical correction later in life appear to experience worse neurocognitive outcomes, but it is unclear whether higher intracranial pressure (ICP) is implicated in this process. The purpose of this study was to elucidate the effect of age at intervention and number of involved cranial sutures on ICP, as well as to assess which cranial suture closure may be more associated with elevated ICP. METHODS The prospective craniof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Increasing age and multisutural involvement are associated with higher incidence of increased ICP. 17 As syndromic cases have multisutural involvement, we had a higher proportion of syndromic cases in our series. The ICP monitoring was found useful in our cases of bicoronal synostoses at the time of reducing the height of the vertex to correct the turret deformity.…”
Section: Discussionmentioning
confidence: 77%
“…Increasing age and multisutural involvement are associated with higher incidence of increased ICP. 17 As syndromic cases have multisutural involvement, we had a higher proportion of syndromic cases in our series. The ICP monitoring was found useful in our cases of bicoronal synostoses at the time of reducing the height of the vertex to correct the turret deformity.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, a recent article12 compared the long-term outcomes of syndromic and nonsyndromic craniosynostosis procedures and, even with its small cohort, found that repeat surgeries were more common in syndromic cases. Further, syndromic patients have a 79.3 times higher risk of multisuture involvement when compared with nonsyndromic patients13; hence the awards in this section.…”
Section: Paediatric Vault Score System Creation Processmentioning
confidence: 99%
“…Of the 28 studies, 17 studies relied on invasive ICP measurements or LP alone to assess ICH. 2,3,[5][6][7][8]18,[20][21][22]24,77,[84][85][86][87]92 A further 11 studies also used indirect methods of ICH assessment in addition to the invasive ICP or LP measurement. [9][10][11][12][13][14][15][16][17]19,23 Twenty-five studies used ICP, 3,[5][6][7][8]18,21,22,24,77,[84][85][86][87]89,93 one study used LP, 18 and 2 used ICP and LP 16,23 to determine ICH.…”
Section: Scoping Review Of Invasive Icp Measurements In Scsmentioning
confidence: 99%
“…Of the 25 studies using ICP, 21 reports both the duration and cut-off value. 2,3,[5][6][7][8][10][11][12][13][14][15]21,22,24,77,[84][85][86][87]89 Of the remaining 4, 1 reports duration but does not report cutoff value, 9 and 3 reports neither duration nor cut-off values used to determine ICH. 17,19,20 In the 3 LP measurement studies, 1 reported duration and cutoff value, 18 1 used the CSF opening pressure for LP measurement, reports cutoff value but not duration of ICP measurement, 16 and the last did not report duration or cutoff values for ICP and LP measurement.…”
Section: Scoping Review Of Invasive Icp Measurements In Scsmentioning
confidence: 99%